Rubella virus infection and associated factors among pregnant women attending the antenatal care clinics of public hospitals in Hawassa City, Southern Ethiopia: a cross-sectional study. Issue 10 (5th October 2017) - Tamirat, Biniam; Hussen, Siraj; Shimelis, Techalew
Abstract : Objective: To assess the seroprevalence of recent/acute and past exposure to rubella virus infection and associated risk factors among pregnant women. Design: A hospital-based cross-sectional study. Setting: The study was conducted in two public hospitals in Hawassa City, Southern Ethiopia. Participants: A total of 422 pregnant women attending antenatal care clinics were selected using a systematic random sampling technique from March to June 2016. Outcome measures: Data on sociodemography and related factors were collected using a structured questionnaire. Blood samples were also collected from each study participant and tested for antirubella IgM and IgG antibodies using ELISA. IgG seropositivity indicates past exposure to rubella (protective immunity). IgM seropositivity indicates recent exposure to rubella (or reinfection). Results: The seroprevalence of antirubella IgM and IgG antibodies was 2.1% and 86.3%, respectively. Thus, the rate of susceptibility to rubella virus infection among pregnant women was found to be 13.7%. A significant association between residence site and IgG seropositivity was observed, where urban dwellers had higher past rubella exposure compared with rural residents (crude OR 6.3; 95% CI 3.29 to 12.14, p<0.001). Conclusion: The high rate of rubella exposure and its similar distribution by sociodemography (except residence site) suggests the continuous transmission and endemicity of the infection in the study area. These findings emphasise the importance of introducing rubella-containing vaccine into routine childhood immunisation programme and vaccinating susceptible women of childbearing age.